MAKNA SIMBOLIK DAN NILAI TRI SILAS DALAM UPACARA ADAT BAKTI PURNAMASARI DI SUKABUMI - Hapidzin, Rivaldi Indra; masunah, Juju; Narawati, Tati; Sunaryo, Ayo (Institut Seni Indonesia Denpasar, 2024)
The Bakti Purnamasari traditional ceremony serves as a vessel for the community to engage in spiritual practices that have been passed down through generations, based on references from the Pantun Pajajaran Bogor manuscripts. Additionally, this traditional ceremony serves as a social platform for communal activities. The Bakti Purnamasari Ceremony transcends beyond a mere series of religious rituals; it becomes a manifestation of cultural continuity and social involvement laden with values and meaning. In this context, the ceremony not only embodies spiritual values but also significantly contributes to the formation of community identity and the reinforcement of social solidarity. In the context of this article, the aim is to describe and analyze the research findings related to symbols, subsequently elaborating on their meanings and the trisilas value namely, silih asih,silih asah, and silih asuh embedded in the Bakti Purnamasari traditional ceremony in Sukabumi. The research methodology employed is descriptive analysis with a qualitative approach. Participants in the study were selected from cultural figures in the city of Sukabumi, deemed valuable sources of information due to their rich knowledge and experiences associated with the Bakti Purnamasari Ceremony. Data collection techniques included observation, interviews, and documentary studies, with data analysis using triangulation. The research results indicate that the symbols in the traditional ceremony are reflected through offerings with intended meanings expressing gratitude for the blessings received. The trisilas values in the Bakti Purnamasari ceremony portray sincere expressions of love and affection, mutual filling or synergy, and a sense of selfless care.